Hematite photoelectrodes for water splitting: Evaluation of the role of film thickness by impedance spectroscopy - Tânia Lopes (2014)
The electrochemical behavior of a-Fe2O3 photoelectrodes prepared by spray pyrolysis with different thicknesses was examined under dark and illumination conditions. The main charge transport phenomena occurring in the PEC cell photoelectrodes were characterized by electrochemical impedance spectroscopy (EIS) operating under dark conditions. The impedance spectra were fitted to an equivalent electrical circuit model for obtaining relevant information concerning reaction kinetics and charge transfer phenomena occurring at the semiconductor/electrolyte interface. A three-electrode configuration was used to carry out the electrochemical measurements allowing a detailed study concerning the double charged layer at the semiconductor/electrolyte interface that arises under dark conditions. The model parameters determined by EIS were then related to the film thickness to assess the role of electronic conduction in the performance of the cell. Moreover, by correlating the sample thickness differences with their electrochemical impedance spectroscopy response, it was possible to discriminate the two main phenomena occurring on semiconductor/electrolyte interfaces of photoelectrochemical systems under dark conditions: the space charge layer and the electrical double layer